Analisis Tindak Pidana Kekerasan Terhadap Anak Dalam Perspektif Sosiologi Hukum - Safaruddin Harefa (Sanskara Hukum dan HAM, 2022)
It is a habit that often views violence against children as a natural thing to happen as a form of parental response to children's behavior. This study uses a type of legal research with a normative juridical research approach and this is because this type of research is a doctrinal legal research.  Through  understanding  from  the  state,  the  functioning  of these  regulations  in  society  can  be  immediately  optimized  in accordance  with  the  objectives  of  the  PKDRT  Law  and  the  Child Protection Law. In addition to laws that tend to provide repressive measures against acts of violence against children, preventive efforts or prevention from the community that can be done is to understand the positionand rights of children that are worthy of respect. Another role is the demand for the community to be sensitive to events that occur around them, especially violence against children, considering that the enactment of the PKDRT Law makes this violence a complaint offense.